Pertimbangan Judex Juris Mengabulkan Alasan Kasasi Terdakwa Dalam Perkara Penyalahgunaan Narkotika - Nugroho, Dinar Agus; Herdyanto., S.H., M.H, Edy (Verstek, 2017)
This research aim is to determine the suitability of consideration judex juris grant reason cassasion defendants in the case of narcotics by members of the military using the Act No. 31 of 1997 on Military Justice. The method used is a normative legal research prescriptive and applied, research with case approach. Sources of legal materials used are primary and secondary legal materials, with materials analysis techniques that are legal syllogism deductive method. Case of drug abuse conducted by Misman Sugianto who is a member of the military has been in Decision Military Court I-07 Balikpapan No. 20-K/PM I-07/AD/III/2014 sentenced penal imprisonment of 11 (eleven) months and fired from military duty. The appeal by Defendant Misman Sugianto was received by the Supreme Court and the Supreme Court Decision No. 25 K/MIL/2015 canceled the previous decision. Based on this study concluded that consideration of the cassation grounds judex juris grant the accused with Article 243 of Law No. 31 of 1997 on Military Justice in conjunction with Article 103 of Law No. 35 of 2009 on Narcotics because the judge considerate yuridist and non yuridist reasons.       Keywords: Cassation, Narcotic, Military Members